2021
DOI: 10.1016/j.abrep.2021.100393
|View full text |Cite
|
Sign up to set email alerts
|

Religious and spiritual beliefs and attitudes towards addiction and addiction treatment: A scoping review

Abstract: Highlights A large proportion of addiction treatment in the U.S. is at least somewhat religious in nature. Some evidence suggests that attitudes toward addiction and addiction treatment are influenced by religious beliefs. Relatively little prior research has examined how religion may shape attitudes toward addiction. Some research suggests that religious beliefs are associated with negative attitudes toward addiction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…21 However, local newspapers and literature on other substance-use disorders have suggested an association between longer term abstinence to substances and increased spirituality and called for further exploration of a link between spirituality, religion and substance use. 29,30,31,32 This should be given more attention in South Africa, as religion is a strong part of communities, particularly in poorer areas. 33 It was suggested that users became easily addicted to Nyaope and found it difficult to commit themselves to rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, local newspapers and literature on other substance-use disorders have suggested an association between longer term abstinence to substances and increased spirituality and called for further exploration of a link between spirituality, religion and substance use. 29,30,31,32 This should be given more attention in South Africa, as religion is a strong part of communities, particularly in poorer areas. 33 It was suggested that users became easily addicted to Nyaope and found it difficult to commit themselves to rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this finding, it seems appropriate to consider the role of spiritual beliefs in relation to the separation-individualization process and the transition from adolescence to adulthood. “Rule-breaking” behavior is common among adolescents during the process of separation-individualization ( 50 ). Chen et al ( 38 ) wrote that their findings also suggest that the relationship between the perceived “judgmental role” of a spiritual power and an adolescent's excessive internet use might not be simply causal, but also interactive, and modified (and motivated) by a normal process of adolescent separation-individualization.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to acknowledge the extensive spectrum of transferability. The challenge of extrapolating research findings to different cultural contexts arises from the considerable diversity in family structures, social mores, and regional cultural practices (Weinandy & Grubbs, 2021). Users are advised to exercise caution when extrapolating these findings beyond the context of Pakistan due to the unique sociocultural influences that affect addiction and the process of recovery.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%